The resurgence of myth in 20th century literature : Tracing the archetypal journey in James Joyce’s A portrait of the artist as a young man - Tahari, Younes Dhiya Eddine; Khalfa, Sayah (University of Ammar Theledji -Laghouat, 2022)
The present research work is an attempt to throw light on the resurgence of myth in the 20th-century literature through tracing the archetypal journey in James Joyce‘s Bildungsroman novel A Portrait of the Artist as a Young Man. A Portrait of the Artist as a Young Man (1916) traces a young man's physical, spiritual, and intellectual development through a skillfully orchestrated sequence of events spread across the novel's five chapters. The primary goal of this work is to trace Stephen Dedalus' journey as a heroic archetype and compare it to the legends of Icarus and Daedalus. As a result, the study is approached from this angle: the archetypal approach, or the archetypal literary criticism.